Роль современной российской песни в формировании лингво-коммуникативной компетенции студентов, изучающих русский язык как иностранный (тема: „Человек – дружба, любовь”) - Woś, Magdalena (Studia Rossica Posnaniensia, 2015)
This article deals with using songs in teaching practical Russian at the college/university level. The author focuses on the positive influence of songs on the development of linguistic and communicative competence. Moreover, the paper attempts to show how effective the process of acquiring Russian as a foreign language can be when supported by authentic musical materials. Furthermore, two exemplary songs and related exercises are proposed.